Weakened amplitude and delayed phase of the future temperature seasonal cycle over China during the twenty‐first century. (13th April 2022) - Hu, Dan; Jiang, Dabang; Tian, Zhiping; Lang, Xianmei
Abstract: The surface air temperature seasonal cycle in China has clearly changed in response to global warming, but its future projection has yet to be studied. Here, we investigate the performance and projection of the temperature seasonal cycle in China in 32 global climate models participating in the Coupled Model Intercomparison Project 6 (CMIP6). The characteristics of the temperature seasonal cycle, as represented by the amplitude and phase, are measured by the Fourier transform. The results show that the CMIP6 models can reasonably capture the observed typical temperature seasonal cycle feature with clear north–south gradients both for amplitude and phase in China. In the twenty‐first century, the models robustly project a delay in the phase across the whole country and a reduction in the amplitude in most of China relative to the reference period. Those changes are similar in the two shared socioeconomic pathway (SSP) scenarios, with overall larger magnitudes in the SSP5‐8.5 scenario than in the SSP2‐4.5 scenario. Projected amplitude changes are mainly linked to surface energy flux changes, especially latent heat flux changes. In response to future global warming, larger increases in the latent heat flux and thus stronger surface evaporative cooling lead to weaker surface warming in summer than in winter, contributing to a decrease in the amplitude of the temperature seasonal cycle in most regions of China. Abstract : Based on the Fourier transform method, the changes in the seasonal cycle of surface air temperature are projected using 32 CMIP6 models under the SSP2‐4.5 and SSP5‐8.5 scenarios. The results show a delay in the phase across the whole country and a reduction in the amplitude in most of China in the 21st century. Those changes are similar between the two scenarios, with overall larger magnitudes in the SSP5‐8.5 scenario than in the SSP2‐4.5 scenario (as shown in figure).